Impact of Dust Shortwave Absorbability on the East Asian Summer Monsoon. Issue 19 (1st October 2020) - Wang, Zheng; Bi, Lei; Jia, Xiaojing; Yi, Bingqi; Lin, Xiubin; Zhang, Feng
Abstract: Dust shortwave absorbability suffers from significant uncertainties. We investigated the radiative effects of dust aerosols from the circum‐Tibet region using four shortwave absorbability schemes and examined their impacts on the East Asian summer monsoon by using the Community Earth System Model (CESM). We adopted superspheroidal models to compute dust aerosol optical properties and found that more absorptive particles have larger asymmetry factor and lower single‐scattering albedo. Meiyu precipitation, as a part of the East Asian summer monsoon, is weakened by dust aerosols, particularly for the convective precipitation. The mechanism is that dust aerosols transported mainly from the Gobi desert radiatively heat the lower atmosphere to the north of the Meiyu rainband and decrease the meridional temperature gradient, leading to the weakening of the midtropospheric westerly jet over the Meiyu rainband, which is important for convection. More absorptive dust aerosols with a stronger radiative heating effect inhibit more convective Meiyu precipitation. Plain Language Summary: The circum‐Tibet region including the Taklimakan and Gobi deserts is the major source region of dust aerosols in East Asia particularly during the spring and summer seasons. Meiyu, as a part of the East Asian summer monsoon, generally occurs from mid‐June to mid‐July and often shows a tilt rain band extending from southwest to east China. The Letter reports on our finding about the relationship between dust shortwave absorbability (the amount of solar radiation absorbed by dust) and Meiyu precipitation. For weakly absorptive dust aerosols, convective Meiyu precipitation is rarely changed by dust aerosols; however, for strongly absorptive dust aerosols, convective Meiyu precipitation is significantly decreased. The impact of dust absorbability on Meiyu precipitation is explained through atmospheric heating rate, temperature, and wind field changes. This Letter emphasizes the urgent need of a more accurate knowledge of dust shortwave absorbability for climate modeling since significant uncertainties of refractive indices exist and new evidences show that Asian dust could be less absorptive than previously believed. Key Points: Dust shortwave absorbability affects single‐scattering albedo and asymmetry factor Dust aerosols inhibit convective Meiyu precipitation depending on absorbability Midtropospheric westerly jet is weakened by dust aerosols causing decreased convective precipitation